ASAS IN DUBIO PRO NATURA DALAM SENGKETA TATA USAHA NEGARA LINGKUNGAN HIDUP: KONSEP DAN IMPLEMENTASINYA - Endri (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2022)
Besides the general principles of good governance (AAUPB) as a measuring instrument for adjudicating cases in the context of environmental administration disputes, there is also In Dubio Pro Natura principle. This study aims to describe the concept and the implementation of In Dubio Pro Natura principle as one of the particular principles known in environmental disputes. To analyze these legal issues, this study will explain the definition and scope of In Dubio Pro Natura principle and how it is applied in the environmental administration case process. This study is important considering that the largest part of environmental law is administrative law so that the Administrative Court plays a major role in the environmental law enforcement process. A complete understanding of the concept of In Dubio Pro Natura principle can influence the process of environmental administration law enforcement by the Administrative Court. The result of this study concludes that In Dubio Pro Natura principle is understood as a concept as well as a guide for judges in examining, deciding, and resolving environmental disputes. If there are judge's doubts whether in scientific uncertainty or legal uncertainty, then judges must side with the interests of the environment (pro natura). This principle also aims to maximize the existence of scientific evidence and competent environmentalists at the proof stage and make a legal invention by applying the principles of environmental policy.